Capacitor, circuit, circuit substrate, device, and capacitor manufacturing method
By designing a specific structure of the tantalum oxide film in the capacitor, including the first part containing fluorine and the second part with a low fluorine concentration, the problem of high dielectric loss tangent in the existing capacitors is solved, and high capacity and low electrical energy are achieved Loss effect.
Patent Information
- Application Number
- CN202380043982.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-31
- Publication Date
- 2025-01-10
AI Technical Summary
When existing capacitors use tantalum oxides containing fluorine, the dielectric loss tangent is high, resulting in an increase in electrical energy loss, making it difficult to meet the needs of high-performance capacitors.
A capacitor is designed, which is arranged between the metal tantalum tantalum and the conductor. The tantalum oxide film contains a first part containing fluorine and a second part with a lower fluorine concentration, and the second part is close to the metal tantalum , through which Structure reduces the dielectric loss tangent.
It effectively reduces the dielectric loss tangent, improves the capacity and performance stability of the capacitor, reduces power loss, and meets the needs of high-performance capacitors.
Smart Images

Figure CN119301720A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a capacitor, a circuit, a circuit substrate, a device, and a method for manufacturing a capacitor. Background Art
[0002] Conventionally, it is known that tantalum oxide containing fluorine is used for capacitors.
[0003] For example, Patent Document 1 describes a solid electrolytic capacitor including a dielectric layer made of tantalum oxide containing fluorine. The dielectric layer is formed by anodic oxidation of an anode made of tantalum in an aqueous solution containing fluorine ions.
[0004] Non-patent document 1 states that the relative dielectric constant of a polycrystalline TaO 2 F thin film is 60 at 1 MHz.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-294402
[0008] Non-patent literature
[0009] Non-patent literature 1: Journal of Materials Chemistry C, (UK), 2020, Issue 14, p.4680-4684 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The present disclosure provides a capacitor which is advantageous from the viewpoint of reducing dielectric loss tangent while using tantalum oxide containing fluorine.
[0012] Means for solving problems
[0013] The capacitor disclosed in the present invention comprises a tantalum metal, a conductor, and a tantalum oxide film disposed between the tantalum metal and the conductor, wherein the tantalum oxide film is disposed in contact with the tantalum metal.
[0014] The tantalum oxide film includes a first portion containing fluorine and a second portion located closer to the metal tantalum than the first portion in the thickness direction of the tantalum oxide film.
[0015] The concentration of fluorine in the second portion is lower than the concentration of fluorine in the first portion.
[0016] Effects of the Invention
[0017] According to the present disclosure, it is possible to provide a capacitor which is advantageous from the viewpoint of reducing dielectric loss tangent while using tantalum oxide containing fluorine. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] [ Figure 1 ] Figure 1 is a cross-sectional view showing an example of a capacitor of the present disclosure.
[0019] [ Figure 2 ] Figure 2 This is a flowchart showing an example of a method for manufacturing a capacitor of the present disclosure.
[0020] [ Figure 3 ] Figure 3 is a cross-sectional view showing another example of the capacitor of the present disclosure.
[0021] [ Figure 4A ] Figure 4A FIG. 2 is a diagram schematically showing an example of a circuit of the present disclosure.
[0022] [ Figure 4B ] Figure 4B This is a diagram schematically showing an example of a circuit board of the present disclosure.
[0023] [ Figure 4C ] Figure 4C The figure schematically shows an example of the device of the present disclosure.
[0024] [ Figure 5 ] Figure 5 Graph showing the XRD pattern of the dielectric film of the sample according to Example 1.
[0025] [ Figure 6 ] Figure 6 The F in the time-of-flight secondary ion mass spectrometry (TOF-SIMS) of the sample involved in Example 1 is shown in FIG. - 、TaO 3- and O - A graph showing the relationship between signal strength and depth in the dielectric film.
[0026] [ Figure 7 ] Figure 7 FIG. 1 is a diagram showing the TOF-SIMS F of the tantalum oxide film of the sample according to Comparative Example 1. - 、TaO 3- and O - A graph showing the relationship between signal strength and depth in the dielectric film.
[0027] [ Fig. 8A ] Fig. 8A Graph showing the relationship between the capacitance and frequency of the capacitor.
[0028] [ Figure 8B ] Figure 8B Graph showing the relationship between the capacitance and frequency of the capacitor.
[0029] [ Fig.9A ] Fig.9A : is a graph showing the relationship between the dielectric loss tangent tanδ and the frequency of the capacitor shown in the example.
[0030] [ Fig. 9B ] Fig. 9B : is a graph showing the relationship between the dielectric loss tangent tanδ and the frequency of the capacitor shown in the example. DETAILED DESCRIPTION
[0031] (Insights that form the basis of this disclosure)
[0032] For example, there is a constant demand for improved processing performance of electronic devices. The performance of electronic components such as capacitors has a great influence on the performance of electronic devices equipped with the electronic components. Therefore, it can be imagined that the demand for small and high-performance capacitors will increase. As a capacitor, for example, electrolytic capacitors are known. In electrolytic capacitors, a dielectric composed of a thin oxide film is formed on the surface of metal aluminum or metal tantalum through chemical conversion treatment of aluminum or tantalum. In electrolytic capacitors, attempts have mainly been made to increase the capacity of the capacitor by increasing the specific surface area of the dielectric. On the other hand, limits can also be observed in such attempts, and it is believed that if a dielectric material with a higher dielectric constant can be developed, the performance of the capacitor can be further improved.
[0033] For example, the polycrystalline TaO2F film described in non-patent document 1 has a higher relative dielectric constant. It is believed that the polycrystalline tantalum fluoride oxide has a different crystal state from that of tantalum oxide Ta2O5, thereby increasing polarization and having a higher relative dielectric constant. In addition, the inventors of the present application have found that tantalum oxide containing fluorine has a higher relative dielectric constant than tantalum oxide Ta2O5 that does not contain fluorine, even when the tantalum oxide is amorphous. Therefore, it can be expected that the capacity of the capacitor can be increased by using tantalum oxide containing fluorine in capacitors. On the other hand, according to the research of the inventors of the present application, it has been found that in a capacitor having a film of tantalum oxide containing fluorine, the dielectric loss tangent of the film will increase. It should be noted that in a capacitor, in order to reduce the loss of electric energy, it is advantageous for the dielectric loss tangent of the dielectric to be low.
[0034] According to patent document 1, the dielectric layer is formed by anodizing an anode composed of tantalum in an aqueous solution containing fluorine ions. It is reported that since the dielectric layer is formed by tantalum oxide containing fluorine, the equivalent series resistance (ESR) of the electrolytic capacitor becomes smaller. On the other hand, according to the research of the inventors of the present application, there are conditions under which the dielectric loss tangent of the film obtained by anodizing tantalum in an aqueous solution containing fluorine ions becomes high. It is known that in such a film, fluorine gathers at the interface between tantalum oxide and elemental tantalum to form a region with a high concentration of fluorine. As a reason for this, the ion diffusion rate of fluoride ions is more than twice the ion diffusion rate of oxide ions. According to the conditions of anodization, fluorine gathers at the interface between tantalum oxide and elemental tantalum to form a region with a high concentration of fluorine. It is believed that since a region with a high concentration of fluorine is formed at the interface between tantalum oxide and elemental tantalum, the dielectric loss tangent of the film becomes high.
[0035] In view of such a situation, the inventors of the present application have repeatedly conducted in-depth research on the composition of a capacitor for reducing the dielectric loss tangent while using tantalum oxide containing fluorine. As a result, it was discovered for the first time that a tantalum oxide film having a specific composition is advantageous for reducing the dielectric loss tangent. Based on this new insight, the inventors of the present application completed the capacitor disclosed in the present invention.
[0036] (Overview of one embodiment of the present disclosure)
[0037] A capacitor according to a first aspect of the present disclosure includes a tantalum metal, a conductor, and a tantalum oxide film disposed between the tantalum metal and the conductor, wherein the tantalum oxide film is disposed in contact with the tantalum metal.
[0038] The tantalum oxide film includes a first portion containing fluorine and a second portion located closer to the metal tantalum than the first portion in a thickness direction of the tantalum oxide film.
[0039] The concentration of fluorine in the second portion is lower than the concentration of fluorine in the first portion.
[0040] According to the first aspect, the fluorine concentration near the metal tantalum of the tantalum oxide film is unlikely to increase. Therefore, although the tantalum oxide film includes the first portion containing fluorine, the dielectric loss tangent of the capacitor is likely to be low.
[0041] In a second aspect of the present disclosure, for example, in the capacitor according to the first aspect, the first portion may be amorphous. According to the second aspect, the capacitor has a high capacitance and can prevent current leakage from a crystalline phase.
[0042] In a third aspect of the present disclosure, for example, in the capacitor according to the first aspect or the second aspect, the first portion may have TaO x Fy The composition represented above can satisfy the condition of 0 < x < 2.5. In this case, the tantalum oxide film easily has a relatively high relative dielectric constant, and the capacitor easily has a high capacitance.
[0043] In the fourth aspect of the present disclosure, for example, in the capacitor according to the third aspect, the above composition can further satisfy the condition of y ≥ 0.015. In this case, the tantalum oxide film more easily has a relatively high relative dielectric constant, and the capacitor more easily has a high capacitance.
[0044] In the fifth aspect of the present disclosure, for example, in the capacitor according to the fourth aspect, the above composition can further satisfy the condition of y ≤ 0.40. In this case, it is easy to prevent fluorine contained in the tantalum oxide film from diffusing into metallic tantalum due to the influence of an electric field, heat, etc., and the tantalum oxide film is not easily denatured. Therefore, the performance of the capacitor is easily stabilized.
[0045] In the sixth aspect of the present disclosure, for example, in the capacitor according to any one of the first to fifth aspects, the concentration of fluorine in the above second portion can be 0.4% or less based on the number of atoms. According to the sixth aspect, the concentration of fluorine near the metallic tantalum in the tantalum oxide film is less likely to become high, and the tangent of the dielectric loss angle of the capacitor is more likely to become low.
[0046] In the seventh aspect of the present disclosure, for example, in the capacitor according to any one of the first to sixth aspects, the above second portion can have a thickness greater than 5 nm and 100 nm or less. According to the seventh aspect, the tantalum oxide film easily has a relatively high relative dielectric constant, and the capacitor easily has a high capacitance. In addition, by making the thickness of the above second portion greater than 5 nm, it is easy to prevent fluorine from diffusing into metallic tantalum, and the tangent of the dielectric loss angle of the capacitor is more likely to become low. It should be noted that the thickness of the natural oxide film formed on the surface of metallic tantalum is usually about 5 nm.
[0047] In the eighth aspect of the present disclosure, for example, the capacitor according to any one of the first to seventh aspects can further include an electrolyte disposed between the above tantalum oxide film and the above conductor. According to the eighth aspect, the capacitor can be configured as an electrolytic capacitor, and the capacitor easily has a high capacitance.
[0048] The circuit according to the ninth aspect of the present disclosure includes the capacitor according to any one of the first to eighth aspects. According to the ninth aspect, the tantalum oxide film of the capacitor includes a first portion containing fluorine, and the tangent of the dielectric loss angle of the capacitor is easily lowered, and the circuit easily exhibits the desired performance.
[0049] The circuit board according to the tenth aspect of the present disclosure includes the capacitor according to any one of the first to eighth aspects. According to the tenth aspect, the tantalum oxide film of the capacitor includes the first portion containing fluorine, and the dielectric loss tangent of the capacitor is easily reduced, so that the circuit board is easy to exhibit desired performance.
[0050] The device according to the 11th aspect of the present disclosure comprises the capacitor according to any one of the 1st to 8th aspects. According to the 11th aspect, the tantalum oxide film of the capacitor includes the first portion containing fluorine, and the dielectric loss tangent of the capacitor is easily reduced, so that the device is easy to exhibit desired performance.
[0051] The method for manufacturing a capacitor according to the twelfth aspect of the present disclosure includes the steps of: performing anodizing on the metal tantalum while the metal tantalum is in contact with an aqueous solution not containing fluorine, and performing anodizing on the tantalum oxide layer on the metal tantalum formed by the anodizing while the tantalum oxide layer is in contact with an aqueous solution containing fluorine, thereby obtaining a tantalum oxide film containing fluorine in the surface region of the tantalum oxide layer. According to the twelfth aspect, a capacitor having a tantalum oxide film containing a portion containing fluorine and having a low dielectric loss tangent can be manufactured.
[0052] (Implementation Method)
[0053] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0054] Figure 1 1 is a cross-sectional view showing an example of a capacitor disclosed in the present invention. Figure 1 As shown, the capacitor 1a includes a metal tantalum 10, a conductor 20, and a tantalum oxide film 30. The tantalum oxide film 30 is arranged in contact with the metal tantalum 10 and between the metal tantalum 10 and the conductor 20. The tantalum oxide film 30 includes a layered first portion 31 containing fluorine and a layered second portion 32. The first portion 31 corresponds to a region (surface region) on the surface side of the tantalum oxide film 30 in the thickness direction of the tantalum oxide film 30. The second portion 32 exists at a position closer to the metal tantalum 10 than the first portion 31 in the thickness direction of the tantalum oxide film 30. In addition, the concentration of fluorine in the second portion 32 is lower than the concentration of fluorine in the first portion 31.
[0055] Since the tantalum oxide film 30 includes the layered first portion 31 containing fluorine, it is easy to have a high relative dielectric constant. Therefore, the capacitor 1a is easy to have a high capacitance. Since the tantalum oxide film 30 has a layered second portion 32 with a low fluorine concentration at a position closer to the metal tantalum 10 than the first portion 31, the fluorine concentration at the interface between the tantalum oxide film 30 and the metal tantalum 10 is not easy to become high. Therefore, the dielectric loss tangent of the capacitor 1a is easy to become low.
[0056] The tangent of the dielectric loss angle of the capacitor 1a is, for example, 0.20 or less at a frequency from 1 Hz to 10 kHz.
[0057] The boundary between the first part 31 and other parts in the tantalum oxide film 30 can form, for example, an interface that can be visually recognized when observing a cross-section of the tantalum oxide film 30 in the thickness direction using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). The boundary between the first part 31 and other parts in the tantalum oxide film 30 can be imaginary, or the interface between the first part 31 and other parts cannot be visually recognized when observing a cross-section of the tantalum oxide film 30 in the thickness direction using SEM or TEM. The boundary between the second part 32 and other parts in the tantalum oxide film 30 can form, for example, an interface that can be visually recognized when observing a cross-section of the tantalum oxide film 30 in the thickness direction using SEM or TEM. The boundary between the second part 32 and other parts in the tantalum oxide film 30 can be imaginary, or the interface between the second part 32 and other parts cannot be visually recognized when observing a cross-section of the tantalum oxide film 30 in the thickness direction using SEM or TEM.
[0058] As long as the second part 32 exists closer to the metallic tantalum 10 than the first part 31 in the thickness direction of the tantalum oxide film 30, the position of the first part 31 is not limited to a specific position. The first part 31 exists, for example, at a position corresponding to a depth of 100 nm or less from the main surface closest to the conductor 20 in the thickness direction of the tantalum oxide film 30.
[0059] The first part 31 can be crystalline or amorphous. Even if the first part 31 is amorphous, the tantalum oxide film 30 easily has a high relative dielectric constant, and the capacitor 1a easily has a high capacitance. For example, in an XRD pattern of an object using Cu-Kα rays at a diffraction angle 2θ from 10° to 50°, when a broad halo pattern is shown, the object can be judged to be amorphous.
[0060] The second part 32 can be crystalline or amorphous.
[0061] As long as the concentration of fluorine in the second part 32 is lower than the concentration of fluorine in the first part 31, the composition of the first part 31 is not limited to a specific composition. In the first part 31, for example, silicon and titanium are not included. The first part 31 has, for example, a composition represented by TaO x F y The composition satisfies, for example, the condition 0 < x < 2.5. In this case, the tantalum oxide film 30 easily has a high relative dielectric constant, and the capacitor 1a easily has a high capacitance.
[0062] In the above composition, for example, the condition of y≥0.015 is satisfied. In this case, the tantalum oxide film 30 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high capacitance. In the above composition, the conditions of y≥0.016, y≥0.017, y≥0.018, y≥0.019, y≥0.02, y≥0.03, y≥0.05, or y≥0.1 may also be satisfied, the condition of y≥0.2 may also be satisfied, and the condition of y≥0.3 may also be satisfied. In addition, the above composition may also satisfy the conditions of 0 < x < 2.5 and 0 < y < 0.015.
[0063] In the above composition, for example, the condition of y≤0.40 may also be satisfied. In this case, it is easy to prevent the fluorine contained in the tantalum oxide film 30 from diffusing into the metallic tantalum 10 due to the influence of an electric field, heat, etc., and the tantalum oxide film 30 is not easily denatured. In the above composition, the conditions of 0 < y≤0.40, 0 < y < 0.40, or 0.015≤y≤0.40 may also be satisfied.
[0064] As long as the concentration of fluorine in the second portion 32 is lower than the concentration of fluorine in the first portion 31, the concentration of fluorine in the second portion 32 is not limited to a specific value. The concentration of fluorine in the second portion 32 is, for example, 0.4% or less on an atomic number basis. In other words, the ratio of the number of fluorine atoms contained in the second portion 32 to the total number of atoms is 0.4% or less. In this case, the concentration of fluorine near the metallic tantalum 10 of the tantalum oxide film 30 is less likely to become high, and the dielectric loss tangent of the capacitor 1a is more likely to become low. The concentration of fluorine in the second portion 32 can be determined, for example, based on the results of TOF-SIMS. It is also possible to combine TOF-SIMS with other analytical methods such as Rutherford backscattering spectrometry (RBS) to determine the concentration of fluorine in the second portion 32.
[0065] The concentration of fluorine in the second portion 32 may also be 0.3% or less, 0.2% or less, or 0.1% or less on an atomic number basis, may also be 0.05% or less, and may also be 0.01% or less.
[0066] F in the TOF-SIMS of the tantalum oxide film 30 - The signal intensity ratio R F is not limited to a specific value. The signal intensity ratio R F is the ratio of the second signal intensity R F2 to the first signal intensity R F1 The first signal intensity R F1 is the signal intensity of F at the depth corresponding to the first portion 31 in the TOF-SIMS of the tantalum oxide film 30 - The second signal intensity R F2 is the signal intensity of F at the depth corresponding to the second portion 32 in the TOF-SIMS of the tantalum oxide film 30- Signal strength ratio R F For example, it is 0.0026 or more. In this case, the fluorine concentration near the metal tantalum 10 of the tantalum oxide film 30 is less likely to increase, and the dielectric loss tangent of the capacitor 1a is more likely to decrease. F It may be 0.005 or more, 0.01 or more, or 0.05 or more. F For example, it is 0.1 or less.
[0067] The thickness of the second portion 32 is not limited to a specific value. Its thickness is, for example, less than 100 nm. In this case, the proportion of the thickness of the second portion 32 in the overall thickness of the tantalum oxide film 30 is likely to be low. Since the fluorine concentration in the second portion 32 is lower than the fluorine concentration in the first portion 31, the second portion 32 is not likely to have a high relative dielectric constant. Therefore, if the proportion of the thickness of the second portion 32 in the overall thickness of the tantalum oxide film 30 is low, the overall relative dielectric constant of the tantalum oxide film 30 is likely to be high, and the capacitor 1a is likely to have a high capacitance.
[0068] The thickness of the second portion 32 may be greater than 5 nm and less than 100 nm. As described above, if the thickness of the second portion 32 is less than 100 nm, the relative dielectric constant of the entire tantalum oxide film 30 is likely to be high, and the capacitor 1a is likely to have a high capacitance. If the thickness of the second portion 32 is greater than 5 nm, it is easy to prevent fluorine in the tantalum oxide film 30 from diffusing into the metal tantalum 10, and the dielectric loss tangent of the capacitor 1a is likely to be low.
[0069] The thickness of the second portion 32 may also be greater than 11 nm, greater than 12 nm, greater than 15 nm, or greater than 20 nm. The thickness of the second portion 32 may also be less than 90 nm, less than 80 nm, or less than 70 nm. The thickness of the second portion 32 may be limited within a specified range. The lower limit of the range is, for example, a value selected from 5 nm, 7 nm, 12 nm, 15 nm, and 20 nm. The upper limit of the range is, for example, a value selected from 70 nm, 80 nm, 90 nm, and 100 nm. When 5 nm is selected as the lower limit, it means that the thickness of the second portion 32 is greater than 5 nm. When a value other than 5 nm is selected as the lower limit, it means that the thickness of the second portion 32 is greater than the selected value. It means that the thickness of the second portion 32 is less than the selected upper limit.
[0070] The method of manufacturing the capacitor 1 a is not limited to a specific method. Figure 2 1 is a flowchart showing an example of a method for manufacturing capacitor 1a. Capacitor 1a is formed, for example, by a method including the following (I) and (II).
[0071] (I) Anodizing the metal tantalum while the metal tantalum is in contact with an aqueous solution not containing fluorine, thereby forming a tantalum oxide layer on the metal tantalum. That is, a tantalum oxide layer ( Figure 2 Step S101).
[0072] (II) Anodizing the metal tantalum while the tantalum oxide layer formed in the above (I) is in contact with an aqueous solution containing fluorine to obtain a tantalum oxide film 30 ( Figure 2 Step S102).
[0073] In anodic oxidation, for example, a voltage of several volts to several hundred volts is applied between the anode and the cathode in a state where an electrolyte is arranged between the anode and the cathode. In the case where metal tantalum is the anode, anions caused by the metal tantalum are bonded to the ionized tantalum to form a chemical conversion film. At this time, there is a case where ions or atoms as impurities from the electrolyte present around the anode are taken into the chemical conversion film. Therefore, in anodic oxidation using metal tantalum as the anode, a film containing only two specific elements such as tantalum and oxygen cannot be formed in essence. Therefore, in the capacitor 1a, other elements such as fluorine can enter the second portion 32 at an impurity level. The so-called impurity level, for example, means that in the second portion 32, other elements such as fluorine other than tantalum and oxygen can be contained at a concentration of less than 0.4% (based on the number of atoms).
[0074] Next, in step S103, the tantalum oxide film 30 is disposed between the metal tantalum and the conductor 20. In other words, in step S103, the conductor 20 is disposed on the side of the tantalum oxide film 30 opposite to the metal tantalum 10. For example, as described above, the capacitor 1a can be obtained.
[0075] In the capacitor 1a, the conductor 20 is not limited to a specific material. The conductor 20 may include valve metals such as aluminum, tantalum, niobium, and bismuth, noble metals such as gold and platinum, or nickel. The conductor 20 may also include a carbon material such as graphite.
[0076] like Figure 1 As shown, the capacitor 1a includes, for example, an electrolyte 40. The electrolyte 40 is disposed between the tantalum oxide film 30 and the conductor 20. In this case, the capacitor 1a is provided as an electrolytic capacitor. In the capacitor 1a, the electrolyte 40 forms, for example, a layer. In the capacitor 1a, the electrolyte 40 may be omitted.
[0077] The electrolyte 40 is not limited to a specific electrolyte. The electrolyte 40 includes, for example, at least one electrolyte selected from an electrolyte solution and a conductive polymer. Examples of conductive polymers are polypyrrole, polythiophene, polyaniline, and derivatives thereof. The electrolyte 40 may also be a manganese compound such as manganese oxide. The electrolyte 40 may also include a solid electrolyte.
[0078] Figure 3 is a cross-sectional view showing another example of the capacitor of the present disclosure. Figure 3 The capacitor 1b shown is constructed in the same manner as the capacitor 1a except for the parts specifically described. The components of the capacitor 1b that are the same as or correspond to the components of the capacitor 1a are marked with the same reference numerals, and detailed descriptions are omitted. The description of the capacitor 1a is also applicable to the capacitor 1b as long as there is no technical contradiction.
[0079] like Figure 3 As shown, in the capacitor 1b, at least a portion of the metal tantalum 10 is porous. With such a structure, the surface area of the metal tantalum 10 is easily increased, and the capacitor 1b is easily provided with a high capacitance. Such a porous structure can be formed, for example, by etching of metal foil and sintering of powder.
[0080] like Figure 3 As shown, a tantalum oxide film 30 is arranged on the surface of the porous part of the metal tantalum 10. As described above, the tantalum oxide film 30 is formed by, for example, anodic oxidation. An electrolyte 40 is arranged in a manner to fill the gaps around the porous part of the first electrode 10. The electrolyte 40, for example, contains at least one electrolyte selected from manganese oxide, an electrolyte solution and a conductive polymer. Examples of conductive polymers are polypyrrole, polythiophene, polyaniline and their derivatives. The electrolyte 40 may also be a manganese compound such as manganese oxide. The electrolyte 40 may also contain a solid electrolyte. In the capacitor 1b, for example, a cathode is formed by the conductor 20 and the electrolyte 40. The conductor 20 may contain, for example, a solidified material of a paste containing silver, a carbon material such as graphite, or both of the above-mentioned solidified material and the carbon material.
[0081] Figure 4A Schematically showing an example of a circuit of the present disclosure. Circuit 3 includes capacitor 1a. Circuit 3 may be an active circuit or a passive circuit. Circuit 3 may be a discharge circuit, a smoothing circuit, a decoupling circuit, or a coupling circuit. Since circuit 3 includes capacitor 1a, circuit 3 can easily exhibit desired performance. For example, in circuit 3, noise can be easily reduced. Circuit 3 may also include capacitor 1b.
[0082] Figure 4B FIG. 1 is a diagram schematically showing an example of a circuit substrate of the present disclosure. Figure 4BAs shown, the circuit substrate 5 includes a capacitor 1a. For example, the circuit 3 including the capacitor 1a is formed in the circuit substrate 5. Since the circuit substrate 5 includes the capacitor 1a, the circuit substrate 5 can easily exhibit the desired performance. The circuit substrate 5 can be a built-in board or a motherboard. The circuit substrate 5 can also include a capacitor 1b.
[0083] Figure 4C FIG. 1 is a diagram schematically showing an example of a device of the present disclosure. Figure 4C As shown, the device 7 has a capacitor 1a. The device 7, for example, has a circuit substrate 5 including the capacitor 1a. Since the device 7 has the capacitor 1a, the device 7 can easily exert the desired performance. The device 7 can be an electronic device, a communication device, a signal processing device, or a power supply device. The device 7 can be a server, an AC adapter, an accelerator, or a flat-panel display such as a liquid crystal display device (LCD). The device 7 can be a USB charger, a solid-state hard disk (SSD), an information terminal such as a PC, a smartphone, and a tablet computer, or an Ethernet switch. The device 7 can also have a capacitor 1b.
[0084] Example
[0085] Hereinafter, the present disclosure will be described in more detail using examples. It should be noted that the following examples are for illustration only and the present disclosure is not limited to the following examples.
[0086] <Example 1>
[0087] The metal tantalum was immersed in a container filled with acetone and then ultrasonically cleaned for 10 minutes to clean the surface of the metal tantalum. Then, the acetone adhering to the surface of the metal tantalum was evaporated, and the surface of the metal tantalum was cleaned with pure water. Then, the metal tantalum was dried in the air.
[0088] In an aqueous solution to which H3PO4 is added, metal tantalum and platinum foil as a counter electrode are arranged at a predetermined interval. A portion of the metal tantalum not immersed in the aqueous solution is connected to the positive electrode of the power supply device, and a portion of the platinum foil not immersed in the aqueous solution is connected to the negative electrode of the power supply device. Current is passed from the power supply device under a constant voltage state, and a voltage of 64V is applied between the metal tantalum and the counter electrode for 30 minutes. An electrochemical reaction is caused on the surface of the metal tantalum as an anode to obtain an oxide film. The metal tantalum formed with the oxide film is taken out from the aqueous solution, washed with pure water, and dried in the atmosphere.
[0089] Next, in the NH4HF2 aqueous solution, a metal tantalum having an oxide film is arranged as an anode, and a platinum foil is arranged as a cathode, and a portion of the anode and cathode that are not immersed in the aqueous solution are connected to the positive and negative electrodes of the power supply device, respectively. The concentration of NH4HF2 in the aqueous solution is 0.5 mol / L. Current is passed from the power supply device under a constant voltage state, and a voltage of 80V is applied between the anode and the cathode for 10 minutes, and an anodic oxidation treatment is performed. Then, the anode after the anodic oxidation treatment is taken out from the aqueous solution, washed with pure water, and dried. By operating as described above, a sample of Example 1 in which a dielectric film is formed on the surface of the metal tantalum is obtained.
[0090] <Example 2>
[0091] The metal tantalum was immersed in a container filled with acetone and then ultrasonically cleaned for 10 minutes to clean the surface of the metal tantalum. Then, the acetone adhering to the surface of the metal tantalum was evaporated, and the surface of the metal tantalum was cleaned with pure water. Then, the metal tantalum was dried in the air.
[0092] In an aqueous solution to which H3PO4 is added, metal tantalum and platinum foil as a counter electrode are arranged at a predetermined interval. A portion of the metal tantalum not immersed in the aqueous solution is connected to the positive electrode of the power supply device, and a portion of the platinum foil not immersed in the aqueous solution is connected to the negative electrode of the power supply device. Current is passed from the power supply device under a constant voltage state, and a voltage of 64V is applied between the metal tantalum and the counter electrode for 30 minutes. An electrochemical reaction is caused on the surface of the metal tantalum as an anode to obtain an oxide film. The metal tantalum formed with the oxide film is taken out from the aqueous solution, washed with pure water, and dried in the atmosphere.
[0093] Next, in the NH4HF2 aqueous solution, a metal tantalum having an oxide film is arranged as an anode, and a platinum foil is arranged as a cathode, and a portion of the anode and cathode that are not immersed in the aqueous solution are connected to the positive and negative electrodes of the power supply device, respectively. The concentration of NH4HF2 in the aqueous solution is 1.0 mol / L. Under a constant voltage state, a current is passed from the power supply device, and a voltage of 80 V is applied between the anode and the cathode for 10 minutes to perform an anodic oxidation treatment. Then, the anode after the anodic oxidation treatment is taken out from the aqueous solution, washed with pure water, and dried. By operating as described above, a sample of Example 2 in which a dielectric film is formed on the surface of the metal tantalum is obtained.
[0094] <Comparative Example 1>
[0095] The metal tantalum was immersed in a container filled with acetone and then ultrasonically cleaned for 10 minutes to clean the surface of the metal tantalum. Then, the acetone adhering to the surface of the metal tantalum was evaporated, and the surface of the metal tantalum was cleaned with pure water. Then, the metal tantalum was dried in the air.
[0096] Next, in the NH4HF2 aqueous solution, metal tantalum is configured as an anode, and platinum foil is configured as a cathode, and a portion of the anode and cathode that are not immersed in the aqueous solution are connected to the positive and negative electrodes of the power supply device, respectively. The concentration of NH4HF2 in the aqueous solution is 0.5 mol / L. Current is passed from the power supply device under a constant voltage state, and a voltage of 80V is applied between the anode and the cathode for 10 minutes, and anodization treatment is performed. Then, the anode after the anodization treatment is taken out from the aqueous solution, washed with pure water, and dried. The operation is performed as described above to obtain a sample involved in Comparative Example 1 in which a dielectric film is formed on the surface of the metal tantalum.
[0097] <Comparative Example 2>
[0098] The metal tantalum was immersed in a container filled with acetone and then ultrasonically cleaned for 10 minutes to clean the surface of the metal tantalum. Then, the acetone adhering to the surface of the metal tantalum was evaporated, and the surface of the metal tantalum was cleaned with pure water. Then, the metal tantalum was dried in the air.
[0099] In an aqueous solution to which H3PO4 is added, a metal tantalum as an anode and a platinum foil as a cathode are arranged at a predetermined interval. The anode and a portion of the cathode that are not immersed in the aqueous solution are connected to the positive and negative electrodes of a power supply device, respectively. A current is passed from the power supply device under a constant voltage state, and a voltage of 80V is applied between the anode and the cathode for 30 minutes. An electrochemical reaction is caused on the surface of the metal tantalum as an anode to obtain a dielectric film as an oxide film. The metal tantalum formed with the oxide film is taken out of the aqueous solution, washed with pure water, and dried in the atmosphere. By operating as described above, a sample involved in Comparative Example 2 having a dielectric film formed of tantalum oxide that does not contain fluorine is obtained.
[0100] (X-ray diffraction measurement)
[0101] An X-ray diffraction (XRD) apparatus Smartlab manufactured by Rigaku Corporation was used to obtain an XRD pattern based on 2θ / θ scanning of the dielectric film of the sample involved in Example 1. Cu-Kα rays were used as the X-ray source, the voltage was adjusted to 40 kV, the current was adjusted to 30 mA, and the scanning speed was adjusted to 10 deg. / min. Figure 5 FIG. 2 shows the XRD pattern of the dielectric film of the sample according to Example 1. Figure 5 In the XRD pattern shown, no peak derived from the crystal structure was confirmed, indicating that the tantalum oxide film of the sample according to Example 1 was amorphous.
[0102] (Elemental composition analysis)
[0103] RBS was performed on samples made from the surface of the dielectric layer of the samples involved in Example 1 and Example 2 using a Rutherford backscattering spectrometer (RBS) device Pelletron 5SDH-2. In RBS, an ion beam is irradiated onto the sample under specified conditions to obtain an RBS spectrum. According to the obtained RBS spectrum, the ratio of the number of fluorine atoms to the number of tantalum atoms in the surface of the dielectric layer of the sample involved in Example 1 is 0.06, and the ratio of the number of fluorine atoms to the number of tantalum atoms in the surface of the dielectric layer of the sample involved in Example 2 is 0.40. According to the obtained RBS spectrum, the composition of the surface of the dielectric layer of the sample involved in Example 1 is TaO 2.47 F 0.06 The composition of the surface of the dielectric layer of the sample in Example 2 is TaO 2.30 F 0.40 .
[0104] (TOF-SIMS)
[0105] A fragment of a predetermined size was cut out from the sample involved in Example 1, and a sample for TOF-SIMS was prepared by embedding with a resin. Using a TOF-SIMS device TOF.SIMS5 manufactured by ION-TOF, a sample prepared from the sample involved in Example 1 was subjected to TOF-SIMS, and a composition analysis in the depth direction of the oxide film of the dielectric film was performed. In TOF-SIMS, a Bi beam was used as a primary ion beam. O2 was used as a sputtering ion species. Figure 6 The TOF-SIMS results of the samples in Example 1 are shown in FIG. - 、TaO 3- and O - A graph showing the relationship between signal strength and depth in the dielectric film. Figure 6 In FIG. 5 , the vertical axis represents the signal intensity of each ion, and the horizontal axis represents the depth in the dielectric film.
[0106] About the sample according to Comparative Example 1, TOF-SIMS was performed in the same manner as in Example 1. Figure 7 The TOF-SIMS results of the samples in Comparative Example 1 are shown in FIG. - 、TaO 3- and O - A graph showing the relationship between signal strength and depth in the dielectric film. Figure 7 In FIG. 5 , the vertical axis represents the signal intensity of each ion, and the horizontal axis represents the depth in the dielectric film.
[0107] according to Figure 6The dielectric film of the sample involved in Example 1 is formed on metal tantalum, and it is understood that it includes a portion with a high fluorine concentration and a portion with a low fluorine concentration. The portion with a high fluorine concentration exists from the surface of the dielectric film to a depth of about 60nm. On the other hand, the portion with a low fluorine concentration exists from a depth of about 75nm to a depth of about 150nm in the dielectric film. - From the signal intensity of , it can be understood that the fluorine concentration in this part is less than 0.5% based on the number of atoms. The fluorine concentration in the part with high fluorine concentration and the part with low fluorine concentration each varies little. - The signal strength R F2 The TOF-SIMS F of the fluorine concentration-high portion of the tantalum oxide film 30 - The signal strength R F1 The ratio is about 0.1 or less. Figure 6 It can be understood that the depth of about 150 nm or more corresponds to the metal tantalum. No increase in fluorine concentration was observed at the boundary between the metal tantalum and the dielectric film.
[0108] On the other hand, according to Figure 7 , it can be understood that the dielectric film of the sample involved in Comparative Example 1 exists from its surface to a depth of about 180nm. In the sample involved in Comparative Example 1, an increase in fluorine concentration was confirmed at the boundary between metal tantalum and the dielectric film. It is believed that this is because the diffusion rate of fluoride ions is much faster than the diffusion rate of oxide ions. Therefore, before the tantalum oxide film is formed by anodic oxidation, the diffusion of fluoride ions to metal tantalum and the generation of tantalum fluoride occur. The tantalum fluoride generated by the above operation lacks electrical insulation and will reduce the characteristics of the dielectric required for the capacitor. In addition, since such tantalum fluoride exists near the metal tantalum, the formation of the tantalum oxide film becomes uneven, and there is also a concern that the tantalum oxide film will peel off. Therefore, it is difficult to say that the dielectric in which tantalum fluoride exists near the metal tantalum is suitable as a dielectric for capacitors. On the other hand, if a fluorine-free solution is used in advance for chemical conversion treatment as in Example 1, a fluorine-containing tantalum oxide film can be easily formed on the metal tantalum in a manner that will not peel off.
[0109] (Capacitance and dielectric loss tangent)
[0110] The sample of Example 1 was installed in an electrochemical cell manufactured by BAS, and the dielectric properties of the capacitor involved in Example 1 were evaluated by the AC impedance method using platinum as a counter electrode. In this evaluation, an AC voltage was applied to the capacitor involved in Example 1 in an amplitude range of 10 to 100 mV and a frequency range of 1 MHz to 0.1 Hz, and the capacitance was calculated from the resistance value at each frequency. Fig. 8A and Figure 8BIt is a graph showing the relationship between the capacitance of a capacitor and the frequency. Fig. 8A and Figure 8B In the figure, the vertical axis represents capacity and the horizontal axis represents frequency. Figure 8B Yes Fig. 8A A portion of the capacitor is enlarged and shown. Based on the evaluation results, the dielectric loss tangent tanδ of the capacitor according to Example 1 at each frequency was determined. Fig.9A and Fig. 9B It is a graph showing the relationship between the dielectric loss tangent tanδ of a capacitor and the frequency. Fig.9A In FIG. 1 , the vertical axis represents tanδ and the horizontal axis represents frequency. Fig. 9B Yes Fig.9A A portion of the diagram is shown enlarged.
[0111] The sample involved in Example 2 was installed in an electrochemical cell manufactured by BAS, and the capacitance and dielectric loss tangent tanδ of the capacitor involved in Example 2 were obtained by the AC impedance method using platinum as the counter electrode in the same manner as in Example 1. The results are shown in FIG. 8A to FIG. 9B middle.
[0112] The sample involved in Comparative Example 1 was installed in an electrochemical cell manufactured by BAS, and the capacitance and dielectric loss tangent tanδ of the capacitor involved in Comparative Example 1 were obtained by using an AC impedance method with platinum as a counter electrode in the same manner as in Example 1. The results are shown in FIG. 8A to FIG. 9B middle.
[0113] The sample involved in Comparative Example 2 was installed in an electrochemical cell manufactured by BAS, and the capacitance and dielectric loss tangent tanδ of the capacitor involved in Comparative Example 2 were obtained by the AC impedance method using platinum as the counter electrode in the same manner as in Example 1. The results are shown in FIG. 8A to FIG. 9B middle.
[0114] The dielectric layers of the samples of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are formed on metal tantalum with the same surface state, and it can be understood that there is no significant difference in the surface area of the dielectric layer of each sample. Fig. 8A and Figure 8B , the capacitance of the capacitors involved in Example 1, Example 2 and Comparative Example 1 is higher than that of the capacitor involved in Comparative Example 2. The capacitance of the capacitor involved in Comparative Example 1 is high, but Fig.9A and Fig. 9BAs shown, the dielectric loss tangent tanδ of the capacitor involved in Comparative Example 1 is high. Tanδ corresponds to the energy consumed inside the capacitor, and it can be understood that the loss of electric energy is large in the capacitor involved in Comparative Example 1. On the other hand, the dielectric loss tangent tanδ of the capacitor involved in Examples 1 and 2 is low, and is maintained at a value equivalent to the dielectric loss tangent of the capacitor involved in Comparative Example 2. Therefore, comprehensively speaking, it can be understood that the capacitors involved in Examples 1 and 2 are not only excellent in capacity, but also excellent in terms of less loss of electric energy.
[0115] Industrial Availability
[0116] The capacitor according to the present disclosure is advantageous from the viewpoint of reducing dielectric loss tangent.
Claims
1. A capacitor comprising tantalum metal, a conductor, and a tantalum oxide film disposed between the tantalum metal and the conductor, the tantalum oxide film being disposed in contact with the tantalum metal, the tantalum oxide film including a first portion containing fluorine and a second portion existing at a position closer to the tantalum metal than the first portion in the thickness direction of the tantalum oxide film, the concentration of fluorine in the second portion being lower than the concentration of fluorine in the first portion.
2. The capacitor according to claim 1, wherein the first portion is amorphous.
3. The capacitor according to claim 1, wherein the first portion has TaO x F y The composition of the representation, The composition satisfies the condition of 0 < x < 2.
5.
4. The capacitor according to claim 3, wherein the composition further satisfies the condition of y ≥ 0.
015.
5. The capacitor according to claim 4, wherein the composition further satisfies the condition of y ≤ 0.
40.
6. The capacitor according to claim 1, wherein the concentration of fluorine in the second portion is 0.4% or less on an atomic number basis.
7. The capacitor according to claim 1, wherein the second portion has a thickness greater than 5 nm and 100 nm or less.
8. The capacitor according to claim 1, further comprising an electrolyte disposed between the tantalum oxide film and the conductor.
9. A circuit comprising the capacitor according to any one of claims 1 to 8.
10. A circuit board comprising the capacitor according to any one of claims 1 to 8.
11. An apparatus comprising the capacitor according to any one of claims 1 to 8.
12. A method for manufacturing a capacitor, comprising the following steps: anodizing the tantalum metal in a state where the tantalum metal is in contact with an aqueous solution containing no fluorine, anodizing in a state where the tantalum oxide layer on the tantalum metal formed by the anodization is in contact with an aqueous solution containing fluorine to obtain a tantalum oxide film containing fluorine in the surface region of the tantalum oxide layer.
Citation Information
Patent Citations
Solid electrolytic capacitor and its manufacturing method
JP2005294402A